Design of an ergonomic computer mouse based on a case study about Musculosketel Disorder (MSD) - Mohammed Muzakkir, Hanafiah (2007)
Musculoskeletal disorder (MSD) is a new type of disease currently spreading among workers in Malaysia. Nowadays, the important of the research on this disease is to preserve the standard quality of human resource and technology in this modern and competitive world. We did not even realize that a computer mouse actually can trigger this disease that will make we suffer a lot of pain throughout the whole body in our old days. For the first step, the literature on MSD and the distribution of the questionnaires to respondents is important in designing an ergonomic computer mouse based on their needs. After the design being presented, simulation using CosmosXpress and Cosmos Mold Flow Xpress software is conducted in order to give a better understanding about the study.